THE INFLUENCE OF LINGUISTIC INTERFERENCE ON THE STUDY OF A SECOND FOREIGN LANGUAGE - Mariia A. Bilokopytova; Olena Ye. Beresten (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The subject of this paper is the linguistic phenomenon of interference that occurs while studying a second foreign language with reference to the existing knowledge of the first foreign language. The article deals with the pressing topic of language interference. Since the number of bilinguals increases on a daily basis, almost each of them experiences interference. Knowledge of two foreign languages has become commonplace. Linguistic interference is a linguistic phenomenon that can be studied from different perspectives. This paper examined the influence of English as the first or dominant language on the second language which is German, the language that is being studied. Before proceeding to the analysis of the main mistakes that students make due to interference, the authors provide several definitions of linguistic interference. To identify how much is known about this phenomenon, the authors scrutinise several domestic and foreign studies on this topic. It is necessary to mention such authors as B. M. Chojbonova, Z. G. Sideshova, U. Weinreich, L. V. Shcherba, H. Schuchardt, E. Haugen and others. The authors have concluded that the problem of language interference is fairly well understood at the moment. The researchers investigated the influence of language interference on the process of learning of a second foreign language (German); analysed the most common mistakes that occur due to interference in terms of transferring the rules of the English language into German. When learning German as a second foreign language, interference can be observed at several language levels: phonetical, morphological, syntactical and lexical. The analysis has revealed that at the initial stage most of the mistakes are made at the phonetical and graphical levels: nouns are written with an initial lowcase letter; ‘sh’ instead of ‘sch’, and others. At the advanced stage, the study of complex grammatical topics implies the word order in subordinate sentences, when the predicate is placed at the end of the sentence, the frame construction, and the reverse word order. Our analysis has shown that the main mistakes caused by linguistic interference are made at the phonetic, lexical and syntactic levels. In order to avoid a large number of mistakes caused by interference, the authors have proposed several methods. The teacher is supposed to be bilingual and possess sufficient knowledge of grammar and vocabulary of the English language. It is recommend that the lesson is to be organised in such a way that the first foreign language should “help” and not “hinder” the learning of the second foreign language. The teacher is to constantly juxtapose English with German and provide examples of differences between the languages; constantly refer to the grammar of the first language and demonstrate the uniqueness of the second on its basis. If the students see that the prior knowledge provides the opportunity to master the second language, they will not only avoid making mistakes caused by interference, but will also on their own account search for differences between the two languages